THE EFFECT OF COMPENSATION ON WORK-LIFE BALANCE AT PT BFI FINANCE, PALOPO BRANCH - Munawir Munawir; Algi Pradiva M; I Kadek Rio; Putu Wahyu Artawan (Jurnal Mahasiswa Manajemen, 2025)
The objective of this study is to analyze the effect of compensation on work-life balance at PT. BFI Finance, Palopo Branch. The data used in this study consists of both primary and secondary data. Primary data was obtained through the distribution of questionnaires to employees at PT. BFI Finance, Palopo Branch. The study involved 30 respondents, selected using a saturated sampling technique. The analytical tool used is simple linear regression analysis. The results show that compensation has a positive and significant effect on the work-life balance of employees at PT. BFI Finance, Palopo Branch, with a regression coefficient value of 0.428 and a significance level of 0.000 < 0.05. The contribution of compensation to work-life balance is 70.2% (R² = 0.702), indicating that compensation is a major determining factor influencing employees' work-life balance. In terms of compensation, the bonus indicator received the highest perception score (4.10), while salary received the lowest score (3.53), although it is still within a favorable category. Regarding work-life balance, the satisfaction balance indicator had the highest score (3.67), while time balance scored the lowest (3.64). The regression equation Y = -0.632 + 0.428X indicates that each one-unit increase in compensation will improve work-life balance by 0.428 units.